Alterations of Tear Film and Ocular Surface in Children with Type 1 Diabetes Mellitus. (2nd April 2020) - Inanc, Merve; Kiziltoprak, Hasan; Hekimoglu, Rumeysa; Tekin, Kemal; Ozalkak, Servan; Koc, Mustafa; Bayramoglu, Elvan; Zirh, Selim; Yuruker, Sinan; Aycan, Zehra
ABSTRACT: Purpose : To investigate whether diabetes mellitus (DM) affects ocular surface of children with well-controlled type 1 DM. Methods : Sixty-five diabetic patients and 55 age-matched controls enrolled to study. Detailed ocular surface assessment including, ocular surface disease index (OSDI) questionnaire, tear film break-up time (TBUT) analysis, Schirmer test, and conjunctival impression cytologic analysis were performed. Results : Schirmer test and TBUT results were significantly lower in DM group than controls ( p = 0.001, for all). OSDI scores of all participants were within normal range. Impression cytology analysis showed grade 0 changes in all participants and there was no difference between groups for goblet cell density ( p > 0.05). The TBUT results were significantly associated with duration of DM ( r = −0.309, p = 0.036). Conclusion : Diabetic children without symptoms, signs, and definite diagnosis of dry eye still had lower TBUT and Schirmer test results than controls; however, impression cytology analysis was similar in both groups.